Assessment of risk factors of non- communicable diseases among healthcare workers in Nelamangala: a cross sectional study - Ahmed, Mohamed Tanveer; Jadhav, Jyothi; Sobagaiah, Ranganath Timmanahalli (International Journal Of Community Medicine And Public Health, 2018)
Background: India is facing a new challenge of epidemiological health transition where the disease spectrum has changed from communicable diseases to non-communicable diseases. Diabetes mellitus, hypertension, stroke and cardiovascular diseases have emerged as major public health problems. Health care workers considered as mentors to general public are becoming victims to these life style disorders. Hence this study was conducted to assess the risk factors of non-communicable diseases among health care workers. Methods: A cross sectional study was carried out for a period of 2 months- October to November 2016 among 120 health care workers working under the primary health centre’s of Nelamangala. Data was collected by interview method using NCD’s risk factors survey India questionnaire. Results: Among 120 study subjects, males were 14 (11.7%) and females were 106 (88.3%). The mean age of study subjects was 39.19 (8.62). Anganwadi workers were 57 (47.50%), 35 (29.10%) were ASHA workers, 8 (6.60%) were senior health assistants and 20 (16.66%) were junior health assistants. Among these 11 (9.2%) had hypertension. 75 (62.5%) had abnormal waist-hip ratio. 33.3% were overweight and 8.3% were obese. Conclusions: There was an association between physical activity and development of risk factors of NCD’s. Most of them are exposed to second hand smoke i.e. passive smoking. Improved literacy status and creation of awareness about the risk factors and sedentary lifestyle among the health care professionals can protect them for Non communicable diseases.